Strategi Pengembangan Pariwisata Berbasis Masyarakat (Studi Kasus di Perkampungan Wisata Sousu, Kabupaten Wakatobi) - Hidrawati, Hidrawati; Udu, Sumiman; Manan, Abdul; Sahari, Sariamin; Fyka, Samsul Alam (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2020)
This research is based on an effort to implement a community-based tourism approach, generally has the main objective to arrange strategy of community-based tourism development at tourism Sousu Rustic. Specifically, this research has a purpose to identify local characteristics that consist of internal and external elements of Sousu in developing tourism based on community. The research was conducted in March-October 2018 at Tourism Sousu Rustic Matahora Village, South of Wangi-Wangi District, Wakatobi Regency, Southeast Sulawesi. Data in this research consists of primer and secondary data collected by observation, interview, and focus group discussion techniques. The data analyzed qualitatively descriptively by using a matrix SWOT analysis tool and litmus test to identify the most strategy issue at Sousu Tourism development. The result of the research showed that the most strategic issues in Sousu tourism development consist of: community knowledge and skills improvement, funding to community tourism business support, minimize relocation community settlement issues and beach abrasion, and improve tourism exciting and does tourism promotion. To implement the strategies, it needs multi-collaboration between communities as the main actor, local government as a regulator, private sector as donor institution, and NGO as community facilitator.